The Common Move and Step in Research Article Abstracts - Mei Relawati; Yazid Basthomi (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: Move and step are components that can provide effective contribution to overall communicative purpose in research article. This study aims to investigate the moves and steps in 48 abstracts publication from cross-disciplinary study under UM journal website. The design of this study is qualitative research. Swales et.al (2014) and Hyland's (2000) models are used to identify moves and steps occurrence. The result shows that the majority of abstracts use M3 (46 abstracts), M4 (44 abstracts), M2 (40 abstracts). Authors mostly apply step 1 in M2 (40 times), step 1 in M4 (42 times), and step 3 in M3 (35 times). Abstrak: Moves dan Steps adalah komponen yang dapat memberikan kontribusi efektif untuk keseluruhan tujuan komunikasi dalam artikel penelitian. Penelitian ini bertujuan untuk menyelidiki langkah-langkah dan langkah-langkah dalam 48 publikasi abstrak dari studi lintas disiplin di situs web jurnal UM. Desain penelitian ini adalah penelitian kualitatif. Model Swales et.al (2014) dan Hyland (2000) digunakan untuk mengidentifikasi keberadaan moves dan steps. Hasilnya menunjukkan bahwa mayoritas abstrak menggunakan M3 (46 abstrak), M4 (44 abstrak), M2 (40 abstrak). Penulis kebanyakan menerapkan step 1 di M2 (40 kali), step 1 di M4 (42 kali), dan step 3 di M3 (35 kali).